Ius Constituendum Principle of Facing Notary in Making Authentic Deed In the Perspective of Virtual Electronics (Cyber Notary) - Raditya, Ami; Resentia, Regina; Shafa Azzahra, Alicia (Dinasti Research, 2024)
In terms of making authentic deeds in Article 16 paragraph (1) letter m of Law Number 2 of 2014 concerning the Office of Notary explains that the Notary must be physically present and sign the deed in the presence of the face and witnesses, this is the case when compared to common law and civil law countries that have implemented the concept of cyber notary, so how is the legal arrangement expected in the future for the office of notary in Indonesia. This writing uses normative legal research methods with a statutory approach (statue approach) and conceptual approach (conceptual approach). The results show that the legal regulation of the concept of facing a notary in making an authentic deed is contained in Article 15 Paragraph (1), Article 15 Paragraph (3), Article 16 Paragraph (1) Letter m, Article 16 Paragraph (7), Article 16 Paragraph (9), Article 39, Article 40 of Law Number 2 of 2014 concerning the Office of Notary. The concept of facing the making of authentic deeds in the future should be held electronically, taking into account, among others: being subject to and guided by the law, using digital signatures by applying cryptographic technology, authentication of two security keys supported by electronic certification organized by a third party, being responsible for issuing digital certificates, taking responsibility and proving the validity of an electronic document to be used as valid evidence and having a burden of proof that does not conflict with the provisions stipulated in the notary office law, the notary still reads the contents of the deed to the attendees.